Mathematical modelling of morphological transition and spot segregation in continuously-cast high carbon steel billets. (2018) - Chaube, Suryanaman
In this work, the columnar-to-equiaxed transition (CET) and spot segregation phenomena in continuously-cast (CC) high carbon steel billets are investigated. Casting process is simulated for a 125 mm × 125 mm billet using a macroscopic thermal model. An empirical correlation, depicting the effect of melt temperature on heterogeneous nuclei density, is incorporated in the CET model to account for a more realistic variation of CET with melt superheat. A parametric study is also performed to see the influence of casting speed on CET and explore its theoretical limit for plant operation. The model is sufficiently general and can be utilised for different caster designs and processing conditions. Additionally, an attempt is made to estimate the degree of solute segregation in small spots along the billet centreline using a simple microsegregation model. The model predictions are compared with experimental observations on CC high-carbon steel billets and the results are encouraging.